Memoirs of a triumphant faith in Christ fifty years of camping and other activities in serving Christ in New South Wales - Sims, Walter; Sims, Christina, d.1975 (Lawson, NSW Mission Publications of Australia, 1980)
Includes photographs.
Brethren writer.
Keywords: Child evangelism -- Brethren movement -- Australia -- biography; Christian Camping -- Brethren movement -- Australia -- biography